Lexical Values to Albanian Language and the Use of the Foreign Words in Albanian without Criteria (European Journal of Language and Literature, 2015)
This paper aims to show that the Albanian language like all the other languages has great lexically values for all its users at all Albanian speaking territories. Languages evolve and refine in all systems, giving and taking from each - other, when it is necessary . While from the irresponsible users of the Albanian language is noticed an excessive use of uncontrolled foreign word instead of Albanian word , while it is being faded more and more the significance and the beauty of Albanian word . The method used is that of the research on theoretical material and the use of living resources. In this study I have concluded that the Albanian language is an important lexical value and the Albanians should use a foreign word instead of Albanian word, only when it is necessary and required. So, in Albanian we can not have an extreme purification, but neither excessive use of foreign words.